Pandemia da coronavirus. Specializzare i medici non specialisti - Giovanni Maria Pisanu (Publiediting, 2020)
In Italy, for some time there has been a constant shortage of specialized medical staff, in particular in emergency areas such as anaesthesia and intensive care. Specialization schools do not have enough places to allow access to all qualified doctors. The dramatic coronavirus pandemic has highlighted this situation. Specializing "on field" non-specialist doctors can be a way of overcoming what is called the training funnel.